(untitled) (Global Journal of Science Frontier Research, 2020)
This note applies least-squares regression to a cross-section comparison of the total infection numbers of COVID-19 as of a particular date among the fifty states of America to investigate any underlying factors; we also check the Gaussian normality of the time progression of the infection rate.